Assessing cachexia in older patients: Different definitions – But which one is the most practical for clinical routine?. (January 2020) - Zopf, Yurdagül; Schink, Kristin; Reljic, Dejan; Herrmann, Hans J.; Dieterich, Walburga; Kiesswetter, Eva; Sieber, Cornel C.; Neurath, Markus F.; Volkert, Dorothee
Highlights: Older patients with cancer have a higher risk for cachexia. Older patients with and without cachexia differ in body composition. Older patients with cachexia have a higher risk of death. Assessment of weight loss can identify older patients with cachexia. Abstract: Objective: Patients with chronic inflammatory diseases and malignant tumors have an increased risk of cachexia. No consistent definition exists to rapidly identify cachexia in older patients with and without cancer. Methods: One-hundred patients (53% male) aged 70 +  years were included in the study by a university hospital. In addition to the detection of malnutrition and determination of body composition by bioelectrical impedance analysis, cachexia was assessed according to the well-established definitions of Evans (weight loss ≥ 5% within the last 12 months plus additional clinical parameters), Fearon (weight loss > 5% in 6 months) and Bozzetti (weight loss ≥ 10% of habitual weight). After a follow-up of 3.5 years, the mortality rate was recorded. Results: Thirty-three patients had a malignant tumor disease. The patients with a non-malignant underlying disease did not differ in their mental state, physical condition and state of health compared to patients with cancer. A higher percentage of patients with underlying malignancy had cachexia. There were significant differences in the body composition between the patients with or without cachexia. Cachectic patients exhibited a significantly lower skeletal muscle mass and fat mass. The risk of death was increased in cachectic patients of all three cachexia definitions. Conclusion: For clinical daily routine, the assessments by a weight loss according to Fearon and Bozzetti are suggested to be practicable methods to detect cachexia in older patients with and without cancer.